Pendidikan Islam Berbasis Etika Ekologis sebagai Respons terhadap Krisis dan Bencana Lingkungan Global - Muhammad Rifkhi Maulana; Ali Murtadho; Baharudin; Imam Syafei (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Increasingly complex global environmental crises and disasters demand a strategic role for education in building awareness, attitudes, and sustainable actions. Islamic education has strong normative and pedagogical potential to respond to these challenges thru the internalization of ecological ethical values derived from Islamic teachings. This research aims to analyze how Islamic education based on ecological ethics is implemented in response to the global environmental crisis and disasters, as well as to identify pedagogical models, impacts on students, and obstacles in its implementation. This research employs a qualitative approach with a descriptive-analytical design and case studies across several Islamic educational institutions, including pesantren, Islamic schools, and madrasahs. Data was collected through in-depth interviews, observations, and analysis of curriculum documents, and was analyzed thematically. The research findings indicate that educational institutions that explicitly integrate Islamic values such as khalifah, amanah, mizan, and the prohibition of fasad thru practice-based programs such as organic farming, waste management, and reforestation are more effective in shaping students' environmental awareness and behavior. The contextual learning and Project-Based Learning approach combined with fiqh al-bi'ah has been proven to improve students' cognitive, affective, and psychomotor aspects. However, this study also found constraints in the form of a lack of a systematic curriculum, uneven teacher capacity, limited resources, and the absence of consistent evaluation instruments. This research recommends strengthening the curriculum, training educators, and developing an Islamic ecological ethics-based evaluation model to make Islamic education a transformational force in addressing the global environmental crisis.